Neurokinin-1 receptors in the nucleus accumbens shell influence sensitivity to social defeat stress and stress-induced alcohol consumption in male mice - Matthew G. Solomon; Sadie E. Nennig; Mallory R. Cotton; Kimberly E. Whiting; Hannah D. Fulenwider; Jesse R. Schank (Addiction Neuroscience)
Chronic social defeat stress (SDS) is a widely employed preclinical model of depression involving repeated exposure to physical defeats using a resident-intruder model in male mice. Exposure to SDS induces depressive-like phenotypes including anhedonia, social withdrawal, and increased drug and alcohol consumption. Previously, we found that expression of the neurokinin-1 receptor (NK1R) is increased in the nucleus accumbens (NAC) of mice that are sensitive to this stressor and increase their alcohol intake. The NK1R is the endogenous receptor for the neuropeptide substance P (SP) and plays a prominent role in stress, anxiety, and addiction. In the present study, we assessed changes in NK1R protein levels in the NAC shell and implemented viral vector strategies to demonstrate a functional role of the NK1R in sensitivity to SDS. Specifically, we found that NK1R protein levels were increased in the NAC shell following SDS exposure. Next, we found that NK1R overexpression in the NAC shell increased the sensitivity to SDS and stress-induced alcohol consumption. Together, these experiments provide evidence for a role of the NK1R in the NAC shell in the sensitivity to SDS and the subsequent escalation in alcohol intake.